Feasibility and acceptability of HPV self-collection and testing using Xpert® HPV in Botswana - Moses Kitheka (Elsevier, 2019)
Cervical cancer is the leading cause of cancer-related deaths among women in Botswana. The burden of HPV-related disease is exacerbated by the high rate of HIV infection, which has an estimated prevalence of 22.8% among adults aged 15-49. We implemented a demonstration programme to evaluate the feasibility and acceptability of HPV self-collection and testing using Xpert® HPV in Botswana.